Effects of buprenorphine, carprofen and saline on thermal and mechanical nociceptive thresholds in cats - Steagall, Paulo V. M.; Taylor, Polly M.; Brondani, Juliana T.; Luna, Stélio Pacca Loureiro [UNESP]; Dixon, Mike J.; Ferreira, Tatiana H. (Blackwell Publishing, 2007)
To evaluate a prototype pressure stimulus device for use in the cat and to compare with a known thermal threshold device.Eight healthy adult cats weighing between 3.0 and 4.9 kg.Pressure stimulation was given via a plastic bracelet taped around the forearm. Three 2.4 mm diameter ball bearings, in a 10-mm triangle, were advanced against the craniolateral surface of the antebrachium by manual inflation of a modified blood pressure bladder. Pressure in the cuff was recorded at the end point (leg shake and head turn). Thermal threshold was also tested. Stimuli were stopped if they reached 55 degrees C or 450 mmHg without response. After four pressure and thermal threshold baselines, each cat received SC buprenorphine 0.01 mg kg(-1), carprofen 4 mg kg(-1) or saline 0.3 mL in a three period cross-over study with a 1-week interval. The investigator was blinded to the treatment. Measurements were made at 0.25. 0.5, 0.75, 1, 2, 3, 4, 6, 8, and 24 hours after injection. Data were analyzed by using ANOVA.There were no significant changes in thermal or pressure threshold after administration of saline or carprofen, but thermal threshold increased from 60 minutes until 8 hours after administration of buprenorphine (p < 0.05). The maximum increase in threshold from baseline (Delta T-max) was 3.5 +/- 3.1 degrees C at 2 hours. Pressure threshold increased 2 hours after administration of buprenorphine (p < 0.05) when the increase in threshold above baseline (Delta P-max) was 162 +/- 189 mmHg.This pressure device resulted in thresholds that were affected by analgesic treatment in a similar manner but to a lesser degree than the thermal method. Pressure stimulation may be a useful additional method for analgesic studies in cats.
Keywords: analgesia; buprenorphine and carprofen; cats; pain